Achieving a Textbook Outcome in Colon Cancer Surgery Is Associated with Improved Long-Term Survival - Dimitrios K. Manatakis; Maria Tzardi; John Souglakos; John Tsiaoussis; Christos Agalianos; Ioannis D. Kyriazanos; George Pechlivanides; Athanasios Kordelas; Nikolaos Tasis; Nikolaos Gouvas; Evaghelos Xynos (Current Oncology, 2023)
Background: Colon cancer surgery is a complex clinical pathway and traditional quality metrics may exhibit significant variability between hospitals and healthcare providers. The Textbook Outcome (TO) is a composite quality marker capturing the fraction of patients, in whom all desired short-term outcomes of care are realised. The aim of the present study was to assess the TO in a series of non-metastatic colon cancer patients treated with curative intent, with emphasis on long-term survival. Methods: Stage I–III colon cancer patients, who underwent curative colectomy following the Complete Mesocolic Excision principles, were retrospectively identified from the institutional database. TO was defined as (i) hospital survival, (ii) radical resection, (iii) no major complications, (iv) no reintervention, (v) no unplanned stoma and (vi) no prolonged hospital stay or readmission. Results: In total, 128 patients (male 61%, female 39%, mean age 70.7 ± 11.4 years) were included in the final analysis. Overall, 60.2% achieved a TO. The highest rates were observed for “hospital survival” and “no unplanned stoma” (96.9% and 97.7%), while the lowest rates were for “no major complications” and “no prolonged hospital stay” (69.5% and 75%). Older age, left-sided resections and pT4 tumours were factors limiting the chances of a TO. The 5-year overall and 5-year cancer-specific survival were significantly better in the TO versus non-TO subgroup (81% vs. 59%, p = 0.009, and 86% vs. 65%, p = 0.02, respectively). Conclusions: Outcomes in colon cancer surgery may be affected by patient-, doctor- and hospital-related factors. TO represents those patients who achieve the optimal perioperative results, and is furthermore associated with improved long-term cancer survival.